Spontaneously Occurring Small-Colony Variants of Staphylococcus aureus Show Enhanced Clearance by THP-1 Macrophages - Stoneham, Simon M.; Cantillon, Daire M.; Waddell, Simon J.; Llewelyn, Martin J. (Frontiers in Microbiology, 2020)
Staphylococcus aureus is a common cause of chronic and relapsing infection, especially when the ability of the immune system to sterilise a focus of infection is compromised (e.g. because of a foreign body or in the cystic fibrosis lung). Chronic infections are associated with slow-growing colony phenotypes of S.aureus on solid media termed Small Colony Variants (SCVs). Stable SCVs show characteristic mutations in the electron transport chain that convey resistance to antibiotics, particularly aminoglycosides. This can be used to identify SCVs from within mixed-colony phenotype populations of S.aureus. More recently, populations of SCVs that rapidly revert to a ‘wild-type’ colony phenotype, in the absence of selection pressure, have also been described. In laboratory studies, SCVs accumulate through prolonged infection of non-professional phagocytes and may represent an adaptation to the intracellular environment. However, data from phagocytic cells is lacking. In this study, we mapped SCV and wild-type colony populations in axenic growth of multiple well-characterised methicillin-sensitive and methicillin-resistant S.aureus strains. We identified SCVs populations on solid media both in the presence and absence of gentamicin. We generated stable SCVs from Newman strain S.aureus, and infected human macrophages with wild-type S.aureus (Newman, 8325-4) and their SCV counterparts (SCV3, I10) to examine intracellular formation and survival of SCVs. We show that SCVs arise spontaneously during axenic growth, and that the ratio of SCV:wild-type morphology differs between strains. Exposure to the intracellular environment of human macrophages did not increase formation of SCVs over 5 days and macrophages were able to clear stable SCV bacteria more effectively than their wild-type counterparts.